Comparison of Perioperative Outcomes of Holmium Laser Enucleation of the Prostate for Standard (≤149 ml) Versus Very Large (≥150 ml) Prostate Glands: Retrospective Analysis of a Propensity Score Matched Cohort of 326 Patients - Jacob Schmidt; Jorien Krediet; Holger Beutel; Ayoub Hidayat Allah; Nella Gagel; Isabel Lichy; Bernhard Ralla; Maha Ullmann; Robert Peters; Frank Friedersdorff; Martin Kanne (European Urology Open Science)
Background and objective: Our objective was to evaluate whether a very large prostate volume significantly affects the incidence of perioperative complications and compromises outcomes among patients undergoing holmium laser enucleation of the prostate (HoLEP). Methods: We retrospectively analyzed data for 1815 adult patients who underwent HoLEP at Evangelisches Krankenhaus Königin Elisabeth Herzberge, Berlin, between January 2019 and May 2024. Patients were divided into two groups according to their prostate volume: ≤149 ml (group A) and ≥150 ml (group B). Propensity score matching on age, body mass index, American Society of Anesthesiologists physical status, and the presence of an indwelling catheter was used to balance baseline differences. A Mann-Whitney U test was used for comparison of continuous variables between the groups, and a χ2 test for comparison of categorical variables, with p < 0.05 considered statistically significant. Postoperative complications were assessed according to the Clavien-Dindo classification. Key findings and limitations: After propensity score matching, 163 matched cases per group were analyzed. Group B had significantly longer median total operative time (76 vs 47 min; p < 0.001), enucleation time (42 vs 26 min; p < 0.001), coagulation time (11 vs 6 min; p < 0.001), and morcellation time (15 vs 7 min; p < 0.001). Clavien-Dindo grade ≥IIIb complications (8.7% vs 1.2%; p = 0.02) and blood transfusion (2.5% vs 0%; p = 0.045) were significantly more frequent in group B. Catheterization time (1.9 vs 2.0 d; p = 0.01) and the proportion of patients with postoperative residual urine volume ≤50 ml (85.2% vs 80.2%; p = 0.18) were comparable between the groups. Limitations include the retrospective and single-center study design. Conclusions and clinical implications: Prostate volume ≥150 ml is associated with a longer operative time, a higher rate of major complications, and a more frequent need for blood transfusion. Therefore, HoLEP for prostate glands ≥150 ml should be performed in experienced high-volume centers. Patient summary: We compared outcomes of laser surgery for enlarged prostate glands of different sizes. We found that while the surgery is generally effective for very large prostates, it takes longer and has a higher risk of complications in comparison to more typical prostate sizes. However, this procedure is still the best treatment available for prostate enlargement and should be carried out in high-volume hospitals specializing in this treatment.